Pengembangan Media Pembelajaran Fisika Berbasis Android Untuk Meningkatkan Hasil Belajar Siswa Ditinjau Dari Motivasi - Berry Kurnia Vilmala; Mundilarto Mundilarto (PTE FTK UIN Ar-Raniry, 2019)
This study aims to (1) produce an android-based Physics learning media on static fluids materials for senior high school students, (2) know whether the android-based Physics learning media is able to improve the students cognitive learning achievement viewed from the motivation. This study is kind of Research and Development. The product of the development was applied in the experiment class, while the conventional learning was applied in the control class. This study used quasi experiment method by applying the nonequivalent control-group design. This study consisted of (1) planning, (2) designing the product, and (3) developing the product. The study results of this research were that android-based physics learning media is rated good by the materials experts, media experts, Physics teachers, colleagues, and students, and stated as appropriate to be used implemented as physics learning media. Then the research concluded that the Android-based Physics learning media is not able to improve the cognitive learning achievement viewed from the learning motivation.